Analisis Multilevel Faktor Yang Berpengaruh Terhadap Kepatuhan Penggunaan Alat Pelindung Diri Bagi Perawat dan Nakes Lain Pada Masa Pandemi Covid 19 di Rumah Sakit Jiwa Menur Surabaya - Budi Andayani; Indasah Indasah (Poltekkes Kemenkes Semarang, 2022)
Background: Health workers in a hospital environment are very at high risk for infection with diseases that can threaten their health and safety whileworking. Compliance in using PPE should take precedence to provide protection to yourself and to patients. The purpose of the study was to analyze the difference in levels (workspaces) related to the influence of knowledge, working life and supervision of compliance with the use of personal protective equipment in Nurses and Other Health Workers at Menur Surabaya Mental Hospital.Methods: Quantitative research design of analytical observational methods. The population of all paramedics at Menur Mental Hospital was 183 respondents. A sample of 126 respondents with proportional random sampling technique. Independent variables of knowledge, working life and supervision. Variable dependent compliance with the use of Personal Protective Equipment (PPE).Results: The majority of respondents' knowledge was more than the mean of 75 respondents (49.5%). The working period of the respondents was more than 1 year, which was 80 respondents (63.5%). Most of the surveillance on respondents was on the morning sift of 62 respondents (49.2). Compliance of 63 respondents (50.0%). Statistical test results have an influence of knowledge on compliance with the use of personal protective equipment in Nurses and Other Health Workers (p = 0.000) and the effect of working life on compliance with the use of personal protective equipment on Nurses and Other Health Workers (p =0.000). And the influence of supervision on compliance with the use of personal protective equipment on Nurse and (p =0.042). The results of the multivariate analysis showed a significant relationship (p= 0.003). Astatistically significant difference between models without taking into account contextual influences and models that take into account contextual influences (likelihoodratio = 0.0038).Conclusions: It is expected that by having goodknowledge, working life, and supervision of compliance with the use of PPE, paramedics will be more compliant with protection as a prevention of infection transmission.